Assembly of τ protein into Alzheimer paired helical filaments depends on a local sequence motif ((306)VQIVYK(311)) forming β structure - von Bergen, M. (The National Academy of Sciences, 2000)
We have searched for a minimal interaction motif in τ protein that supports the aggregation into Alzheimer-like paired helical filaments. Digestion of the repeat domain with different proteases yields a GluC-induced fragment comprising 43 residues (termed PHF43), which represents the third repeat of τ plus some flanking residues. This fragment self assembles readily into thin filaments without a paired helical appearance, but these filaments are highly competent to nucleate bona fide PHFs from full-length τ. Probing the interactions of PHF43 with overlapping peptides derived from the full τ sequence yields a minimal hexapeptide interaction motif of (306)VQIVYK(311) at the beginning of the third internal repeat. This motif coincides with the highest predicted β-structure potential in τ. CD and Fourier transform infrared spectroscopy shows that PHF43 acquires pronounced β structure in conditions of self assembly. Point mutations in the hexapeptide region by proline-scanning mutagenesis prevent the aggregation. The data indicate that PHF assembly is initiated by a short fragment containing the minimal interaction motif forming a local β structure embedded in a largely random-coil protein.